The Influence of Community Efforts on Malaria Vector Density - Hilarius Yosef Muda Gudipung; R. Azizah (Health Notions, 2017)
Malaria still becomes a public health problem, especially on the outside of Java and Bali. Increasing morbidity rate of malaria is one thing caused by malaria vector that exist in endemic area. This study aimed to study the incidence of malaria cases and the effect of community efforts on malaria vectors density, using the cross sectional design. Subjects were 92 people in endemic and non-endemic villages. The variables were vector density as dependent variable, while mosquito repellent, mosquito breeding sites cleaning, spray mosquito coil as independent variable. Data was analyzed using logistic regression test. The p-value and OR of mosquito repellents were 0.077 and 2.304, p-value and OR of breeding place cleaning were 0.028 and 2.741, while pvalue and OR of spray mosquito were 0.006 and 3.799. Health education activities about malaria disease still need to be improved, to avoid mosquito bites should be understood how to control the mosquito, so mosquito density can be reduced. It is expected that the community participates in the prevention of malaria in their area. Keywords: Malaria, Mosquito, Vector density